THE ROLE OF GOVERNMENT, PRIVATE SECTOR AND HIGHER EDUCATION INSTITUTION IN REDUCING POVERTY IN INDONESIA - Alfi Haris Wanto, Mr. (FIA UB, 2012)
Issues of poverty eradication has been one of the achievements of targets agreed with the Millennium Development Goals (MDGs) by 193 countries in the world and at least 23 UN member states of international organizations in the Millennium Development Groups (MDGs). One of the Compact with the MDGs is the eradication of poverty and hunger. Based on data from the Central Statistics Agency (BPS, 2011) the number of poverty Indonesia is still at 30.02 million persons or 12.5 percent of the percentage of the entire population of Indonesia 237 million people. This paper attempts to explain how the governments efforts in tackling poverty by the policies and programs that have been prepared, and then find a variety of challenges to find solutions to solve the poverty problem. Based on the findings the problem of poverty in Indonesia can be solved with the approach to community empowerment through the strengthening of SMEs by increasing the participation of all stake holders including government, private sector, higher education institutions.